The Role of Drawing in Cultivating Students’ Creativity and Cultural Awareness in Art Education” - Rustamov Axtam Muxtorovich (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article discusses the role of drawing in cultivating students’ creativity, technical skills, and cultural awareness within art education. It explores how structured drawing activities enhance visual literacy, problem-solving, and the integration of traditional motifs. The study highlights that drawing not only develops artistic competencies but also strengthens students’ connection to national heritage and identity.